Pengaruh Penerapan Alat Peraga Melalui Model Pembelajaran Numbered Head Together (NHT) Terhadap Hasil Belajar Siswa Pada Materi Bangun Ruang Sisi Lengkung di Kelas IX SMP Negeri 5 Padangsidimpuan - Pane, Intan Parwati; Nasution, Mariam (IAIN PADANGSIDIMPUAN, 2017)
The background of this research is the low mathematics learning outcomes of class IX students of SMP Negeri 5 Padangsidimpuan because the teacher's learning process is not able to create students 'attention, students' enthusiasm in attending classes is still low, so students have difficulty in answering mathematical problems / problems especially in wakefulness curved side space that causes student learning outcomes not to the maximum. This study aims to determine the effect of the application of teaching aids through the numbered heads together (NHT) learning model on student learning outcomes in the material to construct curved side spaces in class IX SMP Negeri 5 Padangsidimpuan.This study refers to Jerome S. Bruner's learning theory which says that learning mathematics will be more successful if the teaching process is directed at the concepts and structures made in the subject being taught, in addition to the related relationships between concepts and structures .This research is a quantitative research with an experimental method of classical experimental design. The population of this study was all students of class IX of SMP Negeri 5 Padangsidimpuan consisting of 12 classes as many as 297 students, and for the sample taken using cluster random sampling technique which is 48 students. The control class is 24 students and the experimental class is 24 students. The instrument used as a data collector is a test given twice, namely before the pretest and posttest. While for data processing and data analysis is done using the t-test formula.Based on the normality and homogeneity test both classes are normally distributed and homogeneous. The t-test is obtained from the results of hypothesis testing which shows tcount t table, namely 10.007 2.0129. So it can be concluded that Ho is rejected and H1 is accepted, meaning that there is a significant influence between the application of props through the numbered heads together learning model on student learning outcomes in the material to construct curved side spaces in class IX SMP Negeri 5 Padangsidimpuan.